Focus on Succes - Ivan Slimák; Kristina Zgodavova (Kvalita Inovácia Prosperita, 2011)
The Editor wishes to present the need and form of turning the focus of individuals and organisations to success, based on evaluating understanding of the situation, on complex improving the quality of work, production and life, and on awareness of accountability for consequences of one’s actions in the given environment and time. Understood by success is sustained financial and non-financial prosperity, whilst decisive is the evaluating process, the key element is loyalty of natural and physical persons, and the priority is loyalty of external customers. The address is targeted to would-be authors and readers of our Journal interested in engineering and management of quality of mutually correlate entities.